PEMECAHAN PERMASALAHAN SEKTOR AIR LIMBAH DI PERKOTAAN MELALUI PEMBERDAYAAN MASYARAKAT DALAM PROGRAM SANIMAS - Nyi Raden Ruyani; Mira Rosana Gnagey; Ahtu Duriat (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2021)
Dense settlements in urban areas are often not well organized, worsening existing sanitationconditions, in addition to technical, economic and social factors resulting in gaps in theprovision of urban facilities and infrastructure related to wastewater management systems. Theproblem of domestic and industrial waste is a crucial issue related to sustainable environmentalmanagement. Where pollution related to domestic waste has the potential to contaminategroundwater with eColy bacteria due to the rapid development of settlements which is sometimesdifficult to control, while polluting industrial waste has a worse impact on the surrounding environment, it needs to be treated specifically. One concrete example of wastewater problems inurban areas is the builder of a family septic tank that no longer meets the technical requirementsas required in the context of environmental health management, at least 10 meters from the wellcan no longer be met due to limited land in urban areas. This condition is exacerbated by thedisposal of used washing water into the drainage network which should be designated for thedisposal and infiltration of rainwater. Because the capacity of the drainage network is no longerin accordance with the existing dimensions, the impacts that ultimately arise are overflow ofwater from the drainage network, puddles on roads and outbreaks of various diseases, such asdiarrhea, dengue fever, etc. The SANIMAS (Community-Based Sanitation) program is a programto improve quality in the sanitation sector, especially in providing wastewater treatmentinfrastructure, which is intended for communities in slum areas and dense urban areas. Differentfrom the regular sanitation program carried out by the government, in the construction ofSANIMAS, the concept of community empowerment is used to make the community the mainactor in the process of planning, building, operating and maintaining communal sanitationfacilities. With the active role of the community, it is hoped that the community will feelownership so that they do not hesitate to maintain it themselves for the realization of the benefitsof sustainable sanitation facilities.